Immobilization and assessment of heavy metals in chicken manure compost amended with rice straw-derived biochar. Issue 1 (1st January 2021) - Li, Hui; Wu, Wei; Min, Xue; Zhan, Wenyong; Fang, Ting; Dong, Xinju; Shi, Yanhong
ABSTRACT: In this study, a 30-days laboratory experiment was implemented to investigate the impact of additive biochar on the stabilization of heavy metals in chicken manure compost. Results showed that after the addition of rice straw-derived biochar, heavy metals were more stabilized except Cu, of which the residual fractions distinctly decreased due to the interaction with organic functional groups from biochar. Given the bioavailability of heavy metals, the biochar addition at a 10% proportion decreased the concentration of CaCl2-extractable Cr, Zn, Ni, and Cd. Besides, CaCl2-extractable As did not differ significantly between treatments with and without biochar addition. Furthermore, the CaCl2-extractable Cu was higher than the control, in agreement with the observed changes in speciation. Environment pollution assessment by integrating potential ecological risk assessment explicated the chicken manure compost reached avery high-risk pollution level, and decreased with biochar addition. Therein, Cd was the dominant pollutant with very high potential risk.